2004
DOI: 10.1103/physreva.70.012313
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement induced by nonadiabatic chaos

Abstract: We investigate entanglement between electronic and nuclear degrees of freedom for a model nonadiabatic system. We find that entanglement (measured by the von Neumann entropy of the subsystem for the eigenstates) is large in a statistical sense when the system shows ``nonadiabatic chaos'' behavior which was found in our previous work [Phys. Rev. E {\bf 63}, 066221 (2001)]. We also discuss non-statistical behavior of the eigenstates for the regular cases.Comment: 4 pages, 6 figures, submitted to Phys. Rev.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Entanglement, the most intriguing feature of quantum mechanics, is a vital resource for many quantum information applications including quantum computing, quantum cryptography, quantum teleportation, and quantum metrology . Because of the importance of dynamical properties of entanglement, it is worthwhile to investigate the dynamics of entanglement in the molecular systems …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entanglement, the most intriguing feature of quantum mechanics, is a vital resource for many quantum information applications including quantum computing, quantum cryptography, quantum teleportation, and quantum metrology . Because of the importance of dynamical properties of entanglement, it is worthwhile to investigate the dynamics of entanglement in the molecular systems …”
Section: Introductionmentioning
confidence: 99%
“…The strong coupling is critical for the quantum parallelism computation, for example, the strong coupling was found to play an important role in the CNOT (Controlled‐NOT) quantum logic gate . However, some investigations also found that the coupling could induce the decrease of fidelity of quantum gates, as the coupling between the qubit system and the remaining vibrational mode is one important resource of decoherence . That is to say, the function of the strong coupling between different modes is still a debate issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have treated this subject and these works consider Hilbert spaces with low dimensionality. Special attention is attached to double-welled chemical systems, as embodying electronic-vibrational entanglement through the role played by the wavefunction delocalization [17,18], and to entanglement in relation with quantum chaos induced by non-adiabatic interaction due to the breakdown of the Born-Oppenheimer approximation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since the physical devises are open systems and may operate in a non-linear regime, it is a natural question to be asked whether the dynamics of production or distraction of entanglement is related to the dynamical properties of the corresponding classical systems. There are many works dealing with this problem, namely , the connection between entanglement and quantum chaos, [3,6,7,8,4,5,9,10,12,13]. While it seems that there are some controversial results about the distractive or constructive influence of classical dynamics on entanglement , one can classify and understand the conditions for one or the other behavior.…”
Section: Introductionmentioning
confidence: 99%